2016
DOI: 10.1016/j.ultramic.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-state sensitive imaging of cerium dioxide by atomic-resolution low-angle annular dark field scanning transmission electron microscopy

Abstract: Low-angle annular dark field (LAADF) scanning transmission electron microscopy (STEM) imaging is presented as a method that is sensitive to the oxidation state of cerium ions in CeO2 nanoparticles. This relationship was validated through electron energy loss spectroscopy (EELS), in situ measurements, as well as multislice image simulations. Static displacements caused by the increased ionic radius of Ce3+ influence the electron channeling process and increase electron scattering to low angles while reducing sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…In electron microscopy studies it is commonly reported that the surface of CeO 2 nanoparticles are reduced. This observation has been made with direct measurements using STEM-EELS and imaging techniques (Goris et al, 2014; Haigh et al, 2011; Johnston-Peck et al, 2016b; Lin et al, 2014; Spadaro et al, 2016; Turner et al, 2011; Wu et al, 2004), and can be inferred by observing the Ce 3+ concentration in ceria particles is inversely related to diameter (Sims et al, 2018; Spadaro et al, 2016; Wu et al, 2004). To determine if the microscope environment influences the oxidation state of CeO 2 particles the oxygen chemical potential of the ESTEM was changed.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…In electron microscopy studies it is commonly reported that the surface of CeO 2 nanoparticles are reduced. This observation has been made with direct measurements using STEM-EELS and imaging techniques (Goris et al, 2014; Haigh et al, 2011; Johnston-Peck et al, 2016b; Lin et al, 2014; Spadaro et al, 2016; Turner et al, 2011; Wu et al, 2004), and can be inferred by observing the Ce 3+ concentration in ceria particles is inversely related to diameter (Sims et al, 2018; Spadaro et al, 2016; Wu et al, 2004). To determine if the microscope environment influences the oxidation state of CeO 2 particles the oxygen chemical potential of the ESTEM was changed.…”
Section: Resultsmentioning
confidence: 83%
“…This can be understood as atomic static displacements in proximity to oxygen vacancies affecting channeling of the incident electrons along the atomic columns while suppressing coherent scattering. The phenomenon of points defects influencing electron scattering has been covered in-depth elsewhere (Cowley, 1995; Grillo et al, 2008; Hall et al, 1966; Johnston-Peck et al, 2016b; Muller et al, 2004; Perovic et al, 1993; Rossouw et al, 1994). Practically this means under equivalent conditions a HAADF image of CeO 2-x (fluorite structure with oxygen vacancies or anion-deficient fluorite) will exhibit lower intensity (image grayscale values) than CeO 2 (fluorite structure without oxygen vacancies) thereby generating contrast.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique has been used to identify strain fields around interfaces and line defects [15, 16]. It is also sensitive to point defects [17, 18] and has been used to identify regions in CeO 2 nanoparticles that were reduced [19]. By using this imaging technique in combination with EELS we were able to quantitatively assess the effects of electron beam irradiation in CeO 2 nanocubes.…”
Section: Introductionmentioning
confidence: 99%